#TITLE_ALTERNATIVE# - ABDURACHMAN (NIM 12301005), WAHMUB
In microgravity 4D, where the fourth dimension is time, the anomaly that occurred is the time-lapse anomaly as a result of the different of the gravity in time interval. The anomaly that observed at the surface similar with the fluctuation of density and the source geometry at the subsurface. Basically, there's some method in analyzing microgravity 4D data, to choose which method that will we use, we must acknowledge the function of the method and the goal that we want to gain. Which in the case of monitoring the intrusion of sea water and the decrease of the water mass at the subsurface, we can use the second vertical derivative method and forward modeling. In this study, the writers do some simulation of response anomaly microgravity 4D synthetic data that cause by subsidence and the decrease of the water mass at the subsurface, and studying second vertical derivative synthetic data. From these simulations, we can see the result of anomaly microgravity 4D that cause subsidence and the decrease of the water mass at the subsurface, in fact from the study of the second vertical derivative we can clearly separated between anomalies that cause by intrusion of sea water and the decrease of the water mass at the subsurface. For the case study, was held at Semarang-Central Java. With the application of the second vertical derivative method and forward modeling, we have the amount of the decrease of the water mass at the subsurface (on July-November) and how far that the intrusion of the sea water has infiltrate the land.